Feasibility analysis of Sinomenine alleviating fibrosis of filtering bleb after glaucoma filtering surgery: a mini review - Xun, Xin; Liu, Xiyuan; Zhou, Pai; Wu, Chengliang; Peng, Qinghua (Frontiers in Medicine, 2025)
Fibrosis of the filtering bleb remains the predominant cause of glaucoma filtering surgery failure, mediated by interconnected pathological processes including postoperative local inflammation, aberrant fibroblast proliferation, and deposition of the extracellular matrix (ECM). The antimetabolite drugs 5-fluorouracil (5-FU) and mitomycin C (MMC) are effective in preventing filtering bleb fibrosis, but their non-specific cytotoxic effects necessitate the development of targeted therapeutic alternatives. Fibrosis is a group of diseases with similar pathological mechanisms and molecular features. By analyzing evidence of Sinomenine's (SIN) anti-fibrotic effects across multiple organs, this study explores its potential use in glaucoma filtration surgery (GFS) to reduce scarring: (1) SIN inhibits trauma-induced NF-κB activation in Tenon's fibroblasts (TFs), reduces neutrophil and macrophage infiltration, and suppresses cytokine cascades. Besides, SIN targets the phosphatidylinositol-3-kinase (PI3K)/Akt pathway to attenuate macrophage M2 polarization and neutrophil recruitment, thereby interrupting fibrotic progression. (2) SIN suppresses transforming growth factor-β (TGF-β)/Smad3 signaling and inhibits the transdifferentiation of fibroblasts into α smooth muscle actin (α SMA) expressing myofibroblasts (MFs). SIN also blocks fibroblast proliferation and migration via PI3K/Akt/mTORC1 axis inhibition, restraining myofibroblast differentiation—the central pathological event in filtering bleb scarring. SIN shows antifibrotic efficacy, and feasibility studies on its application may offer novel insights into antifibrotic strategies.